Liver Involvement During Flare-ups in Pediatric SLE: Lupus Hepatitis vs. Other Causes - Utama, Adelia Anggraini; Kisworini, Priyanti; Raihan, Raihan (Heca Sentra Analitika, 2023)
Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by production of autoantibodies that can affect multiorgan of the body, including the liver. Liver dysfunction is not part of the SLE classification criteria and rarely found compared to other organs. In patient with SLE with liver involvement signed by abnormal liver enzyme should consider whether it is SLE-associated hepatitis, known as lupus hepatitis, or cause by other entities such as drug-induced hepatitis, or a primary liver disease such as viral hepatitis and autoimmune hepatitis condition that coexisting with SLE. We are reporting a 13-year-old boy that has been diagnosed with SLE who had flare since he discontinued his medication by himself. He presented with jaundice, alopecia, oral ulcers, pale and malaise. Laboratory examination showed anemia, thrombocytopenia, elevated transaminases and bilirubin level. It is important to differentiate the cause of deranged liver function test in patient with SLE, because other entities may present similar to lupus hepatitis, but they have a different management and prognosis.